PERAN GAYA MENGAJAR GURU DALAM MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA DI SEKOLAH DASAR - Manik, Sinthya Dwi Putri; Sianturi, Berliana Y.; Hasnah, Atiqatul; Sitepu, Anestasya Amanda; Mailani, Elvi (Universitas Negeri Medan, 2025)
Education quality is closely related to the effectiveness of teachers’ teaching styles in the learning process. This study aims to explore the role of teachers’ teaching styles in enhancing students’ motivation to learn mathematics in elementary school. The research employed a descriptive qualitative approach. Data were collected through classroom observations and in-depth interviews with a fourth-grade teacher and eight fourth-grade students at SD Negeri 060792 Medan Timur. The findings indicate that teaching styles that actively involve students, consider students’ psychological conditions, and connect mathematical concepts to real-life situations significantly contribute to increased learning motivation. In addition, positive teacher–student interactions and the creation of a safe and supportive classroom environment encourage students to participate more actively and confidently in mathematics learning. The use of contextual teaching approaches, group practices, and interactive activities was found to reduce students’ boredom and foster independent learning. This study concludes that appropriate and varied teaching styles play an important role in motivating elementary school students to learn mathematics. Therefore, teachers are encouraged to apply flexible and student-centered teaching styles to create meaningful and engaging mathematics learning experiences.